Feasibility study of using renewable energy in the management of sports venues in the water and electricity industry of east azerbaijan province and its prioritization with D-number theory - Saeed Rasouli Pareh Yousefian; Jafar Barghi Moghaddam; Hamid Janani; Mohammad Najafzadeh; Afshin Roshan Milani (International Journal of Research in Industrial Engineering)
In this paper, the prioritization and weighting of different methods of using renewable energy, as well as the feasibility of using renewable energy in the management of sports venues in the water and electricity industry of east Azerbaijan province, have been discussed. The D-number theory method has been used to prioritize different renewable energy methods. The information gathered from experts in this field shows that solar energy weighing 0.5345 is the best method for producing electrical energy in sports and welfare venues. Wind energy, with a weight of 0.5183, and water energy, with a weight of 0.5126, are in the next ranks. The indicators used in ranking factors include total costs, energy efficiency, and compatibility with environmental conditions. Based on the results of the feasibility study and the available findings, it can be seen that the total cost of using renewable energy in the sports and welfare venues of East Azerbaijan province is equal to 10093.4 million Rials. Also, the interest return rate of the investment is equal to 19.43%. Therefore, using solar energy as a source of electricity production has technical and economic justification.